The development of japanese language learning for elementary school students based on collaborative learning - Desak Made Sri Mardani; I Wayan Sadyana; Ni Nengah Sukni; Ni Kadek Ayu Adrianti; Putri Ayu Wulandari (Universitas PGRI Madiun, 2022)
Japanese learning is not popular in Indonesia but has important value. In Bali, ten elementary schools have introduced Japanese as an additional skill for students to master Japanese from a young age. Therefore it is necessary to develop learning that follows the characteristics of children and can improve 21st-century skills. This study aims to develop Japanese language learning set for elementary students according to student characteristics, requiring students to collaborate and think critically. This study uses a mixed-method approach paradigm, namely Exploratory Mixed Method Design, which combines qualitative and quantitative approaches using the Four-D R&D design. Learning Set in the form of lesson plans, worksheets, and animation media for Japanese language learning that are produced contain activities that require students to collaborate, which can improve students' 21st-century skills. Based on the validity test results, it can be seen that this learning set has been tested for its effectiveness. The assessments carried out by teachers and students show that the lesson plans, worksheets, and animation media are suitable for learning Japanese at the elementary level. Thus, Japanese teaching teachers at elementary schools can use these learning sets to increase student motivation in learning and can improve 21st-century skills.